Megachange : Economic Disruption, Political Upheaval, and Social Strife in the 21st Century - West, Darrell M., 1954- (Book collections on Project MUSE., 2016)
Slow, incremental change has become a relic of the past. Today's shifts come fast and big, what Darrell West calls megachanges, in which dramatic disruptions in trends and policies occur on a regular basis. Domestically, we see megachange at work in the new attitudes and policies toward same-sex marriage, health care, smoking, and the widespread legalization of marijuana use. Globally, we have seen the extraordinary rise and then collapse of the Arab Spring, the emergence of religious zealotry, the growing influence of nonstate actors, the spread of ISIS-fomented terrorism, the rise of new economic and political powers in Asia, and the fracturing of once-stable international alliances. Long-held assumptions have been shattered, and the proliferation of unexpected events is confounding experts in the United States and around the globe. Many of the social and political institutions that used to anchor domestic and international politics have grown weak or are in need of dramatic reform. What to do? West says that we should alter our expectations about the speed and magnitude of political and social change. We also need to recognize that many of our current governing processes are geared to slow deliberation and promote incremental change, not large-scale transformation. With megachange becoming the new normal, our domestic and global institutions must develop the ability to tackle the massive economic, political, and social shifts that we face.